Successful Endovascular Coil Of Carotid Cavernosus Fistula : Case Report - Mampanini, Rizky Rachmadi; Aiko, Novia; Juananda, Desby; Maryanti, Yossi; Sukiandra, Riki (Syntax Literate, 2026)
Carotid Cavernosus Fistula (CCF) is an uncommon vascular disorder defined by an abnormal communication between the carotid arterial system and the cavernous sinus, resulting in direct arterial blood flow into the venous sinus. CCF may be classified as direct or indirect and occur either spontaneously or secondary to trauma, with varying hemodynamic patterns ranging from high-flow to low-flow lesions. A 29 year old man was admitted to Emergency Department of Arifin Achmad General Hospital with a chief complaint of severe headache that had progressively worsened over the preceding nausea. The patient also developed protrusion of the left eye accompanied by visual loss. According to his family, he had become increasingly drowsy over the past three days, although he ramained responsive when addressed. On physical examination, the left pupil was dilated to 7 mm and showed no direct or consensual light reflex. Proptosis of the left eye was evident. Cranial nerve assessment revealed paresis involving cranial nerves II,III,IV, and VI. A non-contrast head CT scan demonstrated a vascular abnormality in the left cavernous sinus region. Further evaluation with CT angiography suggested carotid cavernous fistula. Digital Subtraction Angiography (DSA) subsequently confirmed the presence of vascular malformation in the left cavernous sinus. This report presents a case study aimed at comprehensively describing the clinical characteristics, pathophysiological mechanisms, and diagnostic approach of Carotid Cavernous Fistula (CCF) in neurological practice. The diagnosis is established through the correlation of clinical findings and imaging modalities, including computed tomography (CT), CT angiography, and cerebral angiography, while taking into account the patient’s clinical condition. Therefore, careful and integrated interpretation of clinical and radiological findings is essential to establish an accurate diagnosis and determine appropriate management.